What does 'secure by design' actually mean?. Issue 8 (August 2020) - Duncan, Rory
Abstract : 'Secure by design' is not a new concept. Much discussed as part of General Data Protection Regulation (GDPR) compliance, it has recently re-emerged as a discipline that's integral to strategic security planning. But what does secure by design really mean? A quick search will bring up plenty of options to choose from, covering everything from IoT security to software development. It's so much more than a tagline, however.